Gastrointestinal symptoms in patients receiving dialysis: A systematic review. Issue 8 (29th July 2018) - Zuvela, Jordan; Trimingham, Claire; Le Leu, Richard; Faull, Randall; Clayton, Philip; Jesudason, Shilpa; Meade, Anthony
Abstract: Aim: The aim of the present study was to describe the prevalence of all gastrointestinal (GI) symptoms reported by dialysis patients, as well as the tools being used for diagnosis. GI symptoms are commonly reported in patients having haemodialysis (HD) and peritoneal dialysis (PD), but there are multiple definitions and assessment tools reported in the literature. Methods: A comprehensive systematic review was undertaken using five databases (Embase, Medline, CINAHL, Psycinfo and Web of Science) between 1996 and 2017. Articles were critically appraised using the Newcastle Ottawa Scale (NOS). Data collected were analyzed in a Microsoft Excel spreadsheet. Results: Thirty studies (24 cross‐sectional, six cohort) met the inclusion criteria. In total 5161 patients were studied (3804 HD and 1507 PD). Fifteen studies included HD, five included PD and 10 included both dialysis modalities. GI symptoms were heterogeneous, with the reported prevalence highly dependent on the definitions used, inclusion/exclusion criteria, assessment tools and methods used. The most prevalent symptoms were constipation, indigestion, abdominal pain and reflux. Medication use and dietary data were poorly reported. The most common tools used were Gastrointestinal Symptom Rating Scale (GSRS), Rome II and Rome III. Constipation was more common in HD patients than PD patients. Indigestion, abdominal pain and reflux were commonly reported in both dialysis modalities. Conclusions: Gastrointestinal symptoms are highly prevalent in people on dialysis; however, the evidence base is limited and further investigation of preventable causes and potential interventions such as medications and diet are required in future research. Summary at a Glance: This article is a systematic review of the prevalence of gastrointestinal symptoms in patients on dialysis. The measures used to assess gastrointestinal symptoms are also identified.